ANALISIS PENERIMAAN AUDIENS TERHADAP FEMINISME DALAM FILM “LA LUNA” - Hidayat, Nurzillah Diannovita; Tutiasri, Ririn Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
La Luna addressed issues of feminism, patriarchy, and gender equality that remain relevant in contemporary society. Different social backgrounds, experiences, and personal values led audiences to interpret the feminist messages in various ways. This study aimed to examine audience reception of feminism in the film La Luna. A qualitative approach using Stuart Hall's reception analysis was employed. Data were collected through in-depth interviews with five purposively selected informants who had watched La Luna and represented diverse backgrounds. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings showed that most informants occupied the dominant-hegemonic position, as they accepted the film's messages regarding gender equality, the rejection of patriarchal culture, and women's empowerment. Several informants were categorized in the negotiated position because they accepted the idea of gender equality while still considering religious and cultural values in their interpretations. No informants were found in the oppositional position. The study concluded that La Luna successfully increased audience understanding and awareness of gender equality while encouraging more critical perspectives toward patriarchal practices.